Recent Insights in Petroleum Science and Engineering 2018
DOI: 10.5772/intechopen.70430
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Dibenzothiophene by Pseudomonas fluorescens (UCP 1514) Leading to the Production of Biphenyl

Abstract: Dibenzothiophene (DBT) is a typical recalcitrant thiophenic sulfur component of fuels, and its desulphurization has been a model reaction in the treatment of these compounds. Based on this information, the potential of Pseudomonas fluorescens (UCP 1514) on the desulfurization of dibenzothiphene was studied, in order to use it for reducing the sulfur content of diesel oil in compliance with environmental regulations. The result of biodegradation by the bacteria was determined by undertaking high-performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Naturally, DBT is a xenobiotic compound and at the elevated level, it had a negative effect on cell growth and desulfurization performance of microorganisms. Such kind of effect was also shown by Thayse et al [29] by providing DBT as the bioavailable source of sulfur to Pseudomonas fluorescens UCP 1514. The bacterium exhibited a maximum of 73% desulfurization when supplied 2 mM of DBT, however, the desulfurization achieved with the consortium IQMJ-5 (current paper) is 80%.…”
Section: Effect Of Dbt Concentrationsupporting
confidence: 64%
“…Naturally, DBT is a xenobiotic compound and at the elevated level, it had a negative effect on cell growth and desulfurization performance of microorganisms. Such kind of effect was also shown by Thayse et al [29] by providing DBT as the bioavailable source of sulfur to Pseudomonas fluorescens UCP 1514. The bacterium exhibited a maximum of 73% desulfurization when supplied 2 mM of DBT, however, the desulfurization achieved with the consortium IQMJ-5 (current paper) is 80%.…”
Section: Effect Of Dbt Concentrationsupporting
confidence: 64%
“…DBT metabolites such as DBTO, DBTO 2 and HBPS were not detected in this study. Similarly, Silva et al 34 confirmed in their investigations that intermediate metabolites including DBTO, DBTO 2 , and HPBS were not discovered by GC-MS analysis, which might be explained by the existence of another pathway for the breakdown of DBT. Therefore, further investigations are required to identify all the metabolites in the 4S pathway.…”
Section: Effect Of Operating Variables On Degradation Of Dbt and Form...mentioning
confidence: 87%
“…Other authors also confirmed that other metabolites of the 4S pathway could not be detected in the experiment. However, they are indicated as postulated metabolites [32][33][34] .…”
Section: Effect Of Operating Variables On Degradation Of Dbt and Form...mentioning
confidence: 99%
“…The two most important pathways identi ed in different bacteria for the desulfurization of DBT are the Kodama and the "4S" pathways (Mohebali et al, 2007, Bordoloi et al, 2016. The Kodama pathway is also called a degradative or ring-destructive pathway because in this pathway the bond between two carbon atoms is broken (Silva et al, 2018). The "4S" pathway is also called a sulfur-speci c pathway in the sense, that the sulfur atom in DBT is released as sul te while the carbon skeleton of DBT remains unchanged, and results in retaining the calori c value of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%